An integrative literature review exploring the impact of alcohol workplace policies. Issue 1 (4th December 2020) - Alfred, Lolita; Limmer, Mark; Cartwright, Susan
Abstract : Purpose: Alcohol workplace policies (AWPs) can help organizations to manage and support employees with alcohol-related problems. Over the last two decades, there has been a slow but steady rise of research on AWPs with some indication that these can contribute to reducing employee excessive consumption. However, there does not appear to be any empirical literature reviews to consolidate and evaluate what this body of evidence says regarding the impact of these policies. The following review seeks to address this gap. Design/methodology/approach: Five electronic databases were searched for papers published between January 1996 and January 2020. To capture additional relevant papers (including those from non-peer reviewed sources), the search was extended to Google Scholar, professional and human resource management websites, trade publications and the website of one United Kingdom (UK)-based alcohol charity. Inclusion and exclusion criteria were used to systematically screen the paper titles, abstracts and full-text records. 14 papers were deemed eligible and therefore included in the integrative review. After extracting data, all 14 papers were appraised for quality and then analysed using the narrative synthesis guide by Popay et al. (2006). Findings: Five themes were identified, namely, Associations between Policy and Consumption Levels/Patterns, Deterrence, Policy and Programme Type, Knowledge and Understanding and Enforcement and Discipline. These themes encapsulated what the included papers concluded about the impact and associated benefits or challenges of AWPs. Research limitations/implications: This review identifies that despite the benefits of AWPs, up to 40% of workplaces do not have these policies in place. Future research needs to explicitly explore the reasons for this. Practical implications: This review highlights that AWPs can benefit employees and workplaces. Therefore, organizations are encouraged to develop and implement AWPs to support health improvement and prevention of alcohol problems in the workplace. Originality/value: This review provides a current synthesis of literature published over the last two decades regarding the impact of AWPs on employees and workplaces.